(untitled) - Davis, Paul (Cambridge, U.K., 1988)
Dictation contains a wealth of new techniques to extend the traditional language-learning activity of dictation. The authors present some thought-provoking answers to such apparently simple questions as: Who chooses the text? Who dictates? Who corrects? What and how do they correct? The activities range from traditional focuses on spelling and punctuation problems to exercise that emphasize personal attitudes and opinions of both teachers and students. Dictation provides: activities suitable for a wide range of levels and ages; example texts for many activities, with permission to copy; opportunities for students to create their own texts; a variety of suggested correction techniques; suggestions for using dictation in teacher training.
Keywords: Dictation ( Educational methods ),Languag and languages; Study and teaching